Evolution of approaches to defense policy in Japan in the post-war period - Plaksin A.D. (Восточная Азия: факты и аналитика)
The article analyzes the role of continuity in the development of Japan's defense sector at the present stage. The study examines the key steps of the Japanese leadership towards strengthening of national security policy against the backdrop of a tendency to gradual transition from the implementation of defensive measures to the formation of a base for offensive operations. The work also emphasizes Washington's serious influence on Tokyo's decision to significantly increase Japan's military power. Particular attention is paid to the current defense course of the Kishida Fumio administration in the context of growing regional threats from China and North Korea. Attempts to pursue a hybrid policy are noted, which involves balancing between promoting measures to strengthen the defense sector and confirming with the anti-war sentiments prevailing among the Japanese population.